Estudio de factibilidad para la apertura de un punto de venta de Accesorios Martinas en Villavicencio (2022)
The main objective of this research project is to carry out a feasibility study for the opening of a new branch of the Martina's Accessories store in the city of Villavicencio, to achieve this objective, different studies are carried out, which allowed establishing the viability of the start-up running of this project. In the market study, aspects such as supply, demand and promotion strategies were taken into account, based on a survey that was carried out on the women of Villavicencio, which allowed validating information and determining strategies; In the technical study, aspects such as plant size, location and project engineering were taken into account, which includes a description of processes, an organizational structure, the requisition of supplies and materials for its start-up and, finally, the design prototype of the plant. plant. For the financial study, the total investment of the project is calculated, projection of sales based on historical data and based on said sales, the cash flows are structured to later make the feasibility evaluation with the VPN, TIR and measure the sensitivity evaluating from a pessimistic and optimistic scenario.